Development Of Automatic Traffic Light Based On Wireless Sensor Networks With Star Topologies - Nadia Khotimatul Husna (JAICT, 2017)
Traffic jam at the intersection is caused by many things such as the number of vehicles that exceed the capacity of the highway, road users who do not obey the rules, or lights on a traffic light that is not in accordance with the road conditions. The government has implemented measures to control congestion solutif at a crossroads in Indonesia, especially in big cities by installing the ATCS (Automatic Traffic Control System) that regulate light traffic lights based on real time conditions crossroads. The weakness of this system still needed the operator to settings the traffic light lamp replacement and maintenance costs are expensive. Therefore, we need a system that can regulate light traffic lights adaptively based on the length of the queue of vehicles. In this project, created a system that is able to set the lights on the traffic light by the long queues of vehicles adaptively based wireless sensor networks. Data from XBee sent with a frequency of 2, 4 Ghz towards the coordinator node, the coordinator node data is then processed by a microcontroller arduino mega to compare the length of the queue between the road and determine the traffic light lights adaptively. The test results show a sensor capable of detecting the vehicle up to a distance of 175 cm, the system can detect the length of the queue as far as 56 meters, and can be changed adaptively in a ccordance long queues of vehicle.